Basal melt derived from a phase-sensitive radar (ApRES) at Fimbulisen, East Antarctica - Lindbäck, Katrin; Moholdt, Geir (Norwegian Polar Institute, 2023)
The dataset consists of 36-h filtered basal melt rates (m/yr) derived from a phase-sensitive radar (ApRES) on Fimbulisen ice shelf, Dronning Maud Land (70 deg S, 0 deg E). If you use the dataset in presentations or publications please also refer to the paper (Lindbäck et al., 2023, in review), where the data is described in more detail. The dataset will be updated if the quality of the data is improved or if new datasets become available.